“There is a community of mind in it”: Quoting Shakespeare in the Eighteenth Century - John Mullan (XVII-XVIII)
This piece argues that quoting from literary works written in English became a habit only in the second half of the eighteenth century. The acceptance and celebration of a vernacular canon of English Literature, with Shakespeare’s drama at its heart, gave rise to the art and pleasure of quoting Shakespeare. Shakespeare came to live in common usage through anthologies of ‘beauties’, and especially through the presence of his work in Johnson’s dictionary. Snatches from his plays also became important in eighteenth-century novels, particularly in Sterne’s Tristram Shandy, which relies on a reader’s knowledge of Shakespeare’s text.